Carbohydrate Antigen 125 Is a Biomarker of the Severity and Prognosis of Pulmonary Hypertension - Zhang, Yi; Jin, Qi; Zhao, Zhihui; Zhao, Qing; Yu, Xue; Yan, Lu; Li, Xin; Duan, Anqi; An, Chenhong; Ma, Xiuping; Xiong, Changming; Luo, Qin; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Emerging evidence has showed that serum carbohydrate antigen 125 (CA 125) levels are associated with the severity and prognosis of heart failure. However, its role in pulmonary hypertension remains unclear. This study aimed to investigate the clinical, echocardiographic, hemodynamic, and prognostic associations of CA 125 in pulmonary hypertension. Methods and Results: We conducted a retrospective cohort study of all idiopathic pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension patients receiving CA 125 measurement in Fuwai Hospital (January 1, 2014–December 31, 2018). The primary end-point was cumulative 1-year clinical worsening-free survival rate. Linear regression was performed to assess the association between CA 125 and clinical, echocardiographic, and hemodynamic parameters. Cox proportional hazards models were used to assess the association between CA 125 and clinical worsening events. Receiver operating characteristic (ROC) curve analysis was performed to determine the predictive performance of CA 125. A total of 231 patients were included. After adjustment, CA 125 still positively correlated with World Health Organization functional class, NT-proBNP, right ventricular end-diastolic diameter, pericardial effusion, mean right atrial pressure and pulmonary arterial wedge pressure; negatively correlated with 6-min walk distance, left ventricular end-diastolic diameter, mixed venous oxygen saturation, and cardiac index. After adjustment, CA 125 > 35 U/ml was associated with over 2 folds increased risk of 1-year clinical worsening. Further, ROC analysis showed that CA 125 provided additional predictive value in addition to the established pulmonary hypertension biomarker NT-proBNP. Conclusion: CA 125 was associated with functional status, echocardiography, hemodynamics and prognosis of pulmonary hypertension.